Effect of land use and land use management on methane oxidation - Wanithunga, Irosha (Kansas State University, 2020)
Methane (CH₄) is a potent greenhouse gas that has increased dramatically since the beginning of the industrial era. According to the IPCC 5th assessment report, global warming potential of CH₄ is 28 times higher than CO₂ for a 100 year time scale. Therefore, it is an utmost importance to investigate the factors that affect the CH₄ budget. Methane oxidation is a biological process that reduces atmospheric CH₄ and is affected by land use and land management. The objectives of this study were to: (i) investigate the biotic and abiotic factors that affect CH₄ oxidation in native tallgrass prairie with ‘prescribe fire’ and (ii) investigate the effect of three land-uses (native, restored prairie and cropland) on CH₄ oxidation across two locations with distinct precipitation regimes in Kansas. The first study was conducted at three selected watersheds (C1A, C3A, and C3B) at the Konza Prairie Biological Station (KPBS) in Manhattan, Kansas. The second study was conducted at the Agricultural Research Center in Hays, KS and the Konza Prairie Biological Station in Manhattan, KS. Laboratory incubation experiments investigated the CH₄ oxidation rate at different soil water contents (Gravimetric Water Content-GWC 9%, 20%, 25%, 30%, and 35%). The CH₄ oxidation rate was maximum at a soil water content of 25%, and CH₄ oxidation decreased at soil water contents of 9% and 35%. The addition of ammonium (NH₄⁺, 50µg N g⁻¹ soil) inhibited CH₄ oxidation by 48%. Higher CH₄ oxidation occurred for a 3-year burned versus annually burned tallgrass prairie. Methane oxidation was correlated with total soil copper content. In the second study, soil samples were collected at a depth of 0-5cm. The soil was measured for NH₄⁺, total C, pH, total Cu, extractable Cu, total PLFA biomass and methanotrophic PLFA biomass. A laboratory incubation study investigated the effect of land use and management on CH₄ oxidation. Higher CH₄ oxidation was measured at Konza (0.033 nmol hr ⁻¹ g⁻¹ soil ) than Hays (0.021 nmol hr ⁻¹ g⁻¹ soil) sites. The highest CH₄ oxidation rate was measured at the Konza restored prairie (0.050 nmol hr ⁻¹ g⁻¹ soil ) and the lowest at the Hays native prairie (0.023 nmol hr ⁻¹ g⁻¹ soil ). Land use had a significant (p<0.05) impact on soil microbial biomass, methanotrophic biomass, soil pH, extractable Cu, and total Cu content. Methane oxidation was significantly correlated to soil pH at the Konza site. Location with soil pH greater than 7 inhibited CH₄ oxidation. Total Cu and CH₄ oxidation were significantly correlated at both sites as Cu is a key factor for methanotrophic enzymatic activity. Further, higher pH decreases available Cu in the soil. Together these results suggest that soil Cu content is a crucial driving factor for CH₄ oxidation.
Keywords: Soil microbial; Land use management; Methane oxidation